Using Jeopardy Strategy to Improve The First Semester Students’ Vocabulary at Pikih Program of UIN Alauddin Makassar 2014/2015 - Muhamad Yahrif (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
The objective of this research was to find out whether or not the use of Jeopardy Strategy can improve the students` vocabulary at the first semester of PIKIH Program of UIN Alauddin Makassar 2014/2015. This research employed quasi experimental method with two groups pre-test and post-test design. There were two variables; they were independent variable (the use of Jeopardy Strategy in teaching vocabulary) and dependent variable (the students` vocabulary). The population of this research was the students of PIKIH Program of UIN Alauddin Makassar 2014/2015 which consisted of 1670 students of 67 groups. The sample of the research consisted of two groups by using purposive sampling technique. The researcher took the forty-two group as experimental class and the thirty-nine group as control class. The instrument of this research was a written vocabulary test used in pre-test and post-test. The result of the data indicated that there was a significant difference between students’ post-test in experimental class and controlled class. The mean score of post-test (74.29) in experimental class was greater than the mean score of post-test (59.96) in controlled class. From t-test, the researcher found that the value of t-test (4.44) was greater than t-table (2.00) at the level of significance 0.05 with degree of freedom (df) = 46. Based on the finding and discussion of the research, the researcher drew a conclusion that the use of Jeopardy Strategy can improve the students` vocabulary at the first semester of PIKIH Program of UIN Alauddin Makassar 2014/2015.